PATTERN OF MEDIA REPORTING OF SUICIDE (Proceedings of the Global Public Health Conference, 2022)
Suicide remains a global public health concern with over 800,000 deaths reported annually. The media play an important role in influencing the attitude of the populace to suicide. It has been widely demonstrated that the way suicides are reported/portrayed may increase or reduce the rate and pattern of suicide in a locality. As such guidelines have been put in place to regulate media reporting. The study aimed at analysing the pattern of online media reportage of Suicides in Nigeria based on established guidelines for responsible reporting. This was a retrospective study involving content analysis of 30 randomly selected online newspapers reporting suicide deaths over the past three years (2018-2021) in Nigeria. A total of 147 suicide reports were identified. Majority of the news media used inappropriate language in reporting the suicide. Majority (89.1%) of suicides were portrayed as criminal acts, 87.1% of the suicides were given undue prominence, 10.2% suicides were sensationalized and about half (49%) of the suicides report were explicitly described. Graphic details of methods used occurred in 28.6% of the suicide reports. Only 14.3% of suicides had a published suicide note. Majority of the news media did not provide correct information about mental ill health and only 4.1% of the reported suicide had additional information on help seeking information. We concluded that much still needs to be done to improve suicide reporting. Relevant stakeholders need to continually collaborate with media outfits to provide trainings in order to increase mental health and suicide literacy, as well as to jointly develop locally applicable and culturally relevant guidelines on reportage.
Keywords: suicide; analysis; media report; media guidelines; pattern; Nigeria